REFLEKSI KONSEP MACAPAT PADA KARAKTERISTIK PENOKOHAN WAYANG TOPENG MALANG - Robby Hidajat (Gelar : Jurnal Seni Budaya, 2011)
Javanese cosmology called macapat, the awareness of the concept of the world (natural) consisting of macrocosm and microcosm. Cosmology that contains the values of local wisdom that forms the personality. Cosmological construct the world in the four winds, associated with the four central figures in Malang Mask Puppet serving Panji story. Linkage with Java cosmology living conception in the minds of his supporters. This understanding is intended to understand the value of education, personality, and culture, to do with the conception underlying the existence of the characters in the play Puppet Mask Malang. Findings in macapat concept is an understanding of the central figure, namely: Flag Asmarabangun, Galuh Candrakirana, Gunungsari, and Klana Sewandana.Key words : Characteristics, Concepts, Macapat, the play, Panji